THE ROLE OF INTELLIGENCE AND SECURITY UNIT IN INTELLIGENCE INVESTIGATION OF DRUGS CRIMINAL ACT PREVENTION IN WONOSOBO DISTRICT POLICE AREA - IRHAM RHOZAN AL FIQRI (Police Studies Review, 2022)
Drug abuse and trafficking are kinds of crime and criminal act that can threaten national interests and security. The Intelligence and Security Unit of Wonosobo District Police, as the executor of early detection task must play a role in preventing drug crimes among the area. Background of this study was The Intelligence and Security Unit only conducted certain operation tasks in preventing drug crime, but did not play a role in preventing it in daily task implementation. This study aimed to describe the implementation of intelligence investigations and the role of the intelligence and security unit of Wonosobo District Police in context of preventing drug crimes. The unit 4 of the intelligence and security unit in the field of state security actually should carry out the early detection tasks, such as intelligence investigations on drug crimes because the State Intelligence played a role in carrying out early detection efforts to prevent any threats might be arised and also threaten national interests and security. Problem description in this study used a qualitative approach with descriptive analysis method. The theories and concepts used in this study include management and role theory, also the concept of intelligence investigation as the analytical tools to describe the implementation of intelligence investigations and the role of its unit in preventing drug crimes at the Wonosobo District Police. The intelligence and security unit of Wonosobo District Police played a role and took part in drug-free operation around the temples by conducting early detection activities for drug crime regard to its prevention. Through the operation, The Intelligence and Security Unit used the main and special intelligence tools as aids in performing intelligence investigations against drug crimes. However, the unit had not played a role yet in preventing drug crimes, except in that operation. The unit should maximize the use of special intelligence tools and be a benefit to drug crimes prevention in Wonosobo District Police area by conducting intelligence investigations and developing networks for drug criminal cases.